On the topology of Sasakian manifolds - Pitiş, Gheorghe (MATHEMATICA SCANDINAVICA, 2003)
The notion of $q$-bisectional curvature of a Sasakian manifold $M$ is defined. It is proved that if $M$ has lower bounded $q$-bisectional curvature and contains a compact invariant submanifold tangent to the structure vector field then $M$ is compact. Myers and Frankel type theorems for Sasakian manifolds with lower bounded and positive $q$-bisectional curvature, respectively, are also given.